The Impact of Economics on Competition Law in New Zealand Some Reflections on the First Decade - Berry, Mark N (Victoria University of Wellington Law Review, 1996)
The economic focus of the Commerce Act 1986 is unique in New Zealand, both in terms of its theoretical foundations and its institutional framework. The author reflects on these features of the Act and the impact that economics has had on the decision-making process. This article reviews the New Zealand landscape in terms of the goals of the Commerce Act, its institutional framework, and the manner in which the strict rules of evidence may be relaxed. It then considers, by using Justice Breyer's framework (in S J Breyer "Economics and Judging: An Afterword on Cooter and Wald" (1987) 50 Law and Contemp Probs 245), how economics has impacted upon the content of rules of law and the proof of specific economic facts. The author concludes with a brief assessment of likely and desirable future trends in New Zealand law, arguing that it was likely that economics would continue to have a major impact on the Commerce Act; aside from in the interpretation of dominance principles, the author argues that the foundations are strongly in place for the continued growth of law and economics in this field.